Laparoscopic Distal Pancreatectomy for Multiple Epithelial Cysts in an Intrapancreatic Accessory Spleen. A Case Report and Review of Literature - Wakasugi, Masaki; Tori, Masayuki; Akamatsu, Hiroki; Ueshima, Shigeyuki; Omori, Takeshi; Tei, Mitsuyoshi; Masuzawa, Toru; Tsujimoto, Masahiko; Nishida, Toshirou (JOP. Journal of the Pancreas, 2013)
Context Accessory spleen is a congenital abnormality consisting of normal splenic tissue in ectopic sites that is found in approximately 10-15% of the general population. However, an intrapancreatic accessory spleen has seldom been reported and multiple epithelial cysts in the intrapancreatic accessory spleen are extremely rare. Case report A 37-year-old woman with no clinical manifestations presented with two cystic lesions in the tail of the pancreas. The tumor markers CA 19-9 (251 U/mL) and SPAN-1 (38 U/mL) were increased. Computed tomography showed a multilocular cyst, 40 mm in size, and a unilocular cyst, 20 mm in size, in the tail of the pancreas and gallstones. The cystic component was hypointense on T1-weighted magnetic resonance images and hyperintense on T2-weighted magnetic resonance images. A laparoscopic distal pancreatectomy was performed with the presumptive diagnosis of a mucinous cystic neoplasm or an intraductal papillary mucinous neoplasm with gallstones. The pathological examination showed that the walls of the two cysts were covered with non-keratinized stratified squamous epithelium, surrounded by normal splenic tissue. The final pathological diagnosis was two epithelial cysts originating from an intrapancreatic accessory spleen. Conclusions Even though multiple masses were detected in the pancreatic tail, the possibility of epithelial cysts originating from an accessory spleen should be considered. Laparoscopic distal pancreatectomy might be a safe and effective procedure and provide good cosmetic result for a benign or low-grade malignant tumor in the pancreas. Image: Laparoscopic view of the mobilization of the spleen and pancreatic tail.